PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP PEMAHAMAN KONSEP IPS SD - M. Ihsan Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar STKIP Al Hikmah Surabaya, 2019)
This study aims to determine the differences in the influence of the make a match learning model compared with expository learning models on the understanding of students' social science concepts. This research uses quasi-experimental research with pretest - posttest control group design. The subjects in this study were students at Tanggul Rejo 2 Public Elementary School in Marabahan District, consisting of class V A totaling 20 students as experimental class and 22 students of class V B as control class in semester II of the academic year 2017/2018. The selection of the experimental class and the control class based on the characteristics of students that are almost the same, by random method. The random results of class V A were selected as the experimental class using the make a match learning model and class V B as the control class using the expository learning model. The data analysis technique used independent sample t-test and paired sample t-test with the help of SPSS 23 for Windows. The results showed that the make a match learning model had a more significant effect than the expository learning model on the understanding of the social studies concept of students in SDN Tanggul Rejo 2 with a significance value of 0,000 <0.05.